Burden of associated comorbidities in autoimmune rheumatic diseases in Indian population: An interim report based on the Indian rheumatology association database - S Chandrashekara; Padmanabha Shenoy; Uma Kumar; Sapan Pandya; Alakendu Ghosh (Indian Journal of Rheumatology)
Aim: The present study is intended to analyze the preliminary interim data to understand the burden of associated comorbidities in autoimmune rheumatic diseases (AIRDS) in the Indian population from the Indian Rheumatology Association database. Materials and Methods: The independent prospective, multicenter, observational study evaluated the preliminary data obtained from 5 centers across India. The data pertaining to comorbidities were collected, as per the definition of the new International Classification Diseases-10 version of the Charlson Comorbidity Index. The details such as socioeconomic status, impairment in the working capability, and their capacity to cope with their job after developing the disease were gathered for selected patients. The patients were broadly classified into five based on diagnosed AIRDS namely rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), seronegative spondyloarthropathy (SpA), psoriasis arthritis (PsA), and scleroderma. The prevalence of different comorbidities was compared between the groups using Chi-square or Fischer-exact test for nonparametric data and analysis of variance for continuous variables. Results: The study considered the data of 1885 for the analysis and 129 patients were excluded due to missing variables and data inconsistency. The socioeconomic distribution of AIRDS indicated that SLE was more prevalent among upper-middle-class followed by SpA (60.3% and 50.94%, respectively). RA and systemic sclerosis (SSc) were more common among the lower-income group, and PsA was common among the upper socioeconomic group. The most common comorbidity found in patients with RA and PsA was hypertension (20.97%, 17.14%), SLE and SSc was thyroid disease (21.49%, 17.78%), and SpA was diabetes (2.96%). Conclusion: AIRDs are associated with the significant burden of comorbidities. Further studies are needed to understand the pattern of prevalence of comorbidities across different age groups.